Facile green synthesis and characterization of Terminalia arjuna bark phenolic–selenium nanogel: a biocompatible and green nano-biomaterial for multifaceted biological applications - Puri, Abhijeet; Mohite, Popat; Patil, Swati; Chidrawar, Vijay R.; Ushir, Yogesh V.; Dodiya, Rajesh; Singh, Sudarshan (Frontiers in Chemistry, 2023)
Biogenic nanoparticle production is in demand as it is secure, has great promise, and is environmental friendly. This study aimed at green synthesis, characterization, and evaluation of Terminalia arjuna selenium nanoparticles (TA-SeNPs) for their antioxidant, antibacterial, anticancer activities, and their incorporation in gel for biomedical applications. The bio-reduction attributes of the T. arjuna (TA) bark extract were utilized to fabricate selenium nanoparticles. The TA bark extract is abundant in phenolics (193.63 ± 1.61 mg gallic acid equivalents/g), flavonoids (88.23 ± 0.39 mg quercetin equivalents/g), and tannins (109.46 ± 1.16 mg catechin equivalents/g), which perform as effective capping and stabilizing agents, thus enabling the fabrication of stable SeNPs. The fabrication of TA-SeNPs was corroborated by UV–visible spectra, which exhibited surface plasmon resonance at 291 nm. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) demonstrated nano-sized spherical TA-SeNPs with an average diameter ranging from 100 to 150 nm. Zeta potential analysis revealed that TA-SeNPs were negatively charged (−26.1 mV). X-ray diffraction presented amorphous TA-SeNPs with a quantification of 82.36 ± 10.2 μg/mL resulting from ICP-AES. The IC50 45.18 ± 0.11 μg/mL for the DPPH assay and 66.51% reducing power capacity values indicated that the TA-SeNPs possessed excellent radical scavenging efficacy. Moreover, the TA-SeNPs exhibited a broad spectrum of antimicrobial activity against potential pathogens. Additionally, the TA-SeNPs exhibited a dose-dependent cytotoxic effect on the MCF-7 breast cancer cell line, with an IC50 of 23.41 μg/mL. Furthermore, the TA-SeNP-incorporated gel showed excellent spreadability, extrudability, and consistency with retention of antimicrobial properties and hydrophilic contact angle. As an outcome, TA-SeNPs offer the possibility of the formulation and growth of sustainably designed green SeNPs that can be produced, conserved, and marketed securely across the globe.